Facebook.com : global marketing opportunities and connectivity - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
This case study investigates the unique marketing opportunities presented by the growing phenomenon of social media. Facebook has vastly increased opportunities to contact and connect with potential customers on an international basis, which causes a range of unique and traditional marketing challenges to arise.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). Facebook.com: Global Marketing Opportunities and Connectivity. In International marketing (pp. 3-5). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Facebook (Firm); Social media -- Economic aspects -- Case studies; Internet marketing -- Case studies